Comparative Pharmacokinetic Study of Two Pyrrolizidine Alkaloids Lasiocarpine and Heliotrine in Rats - Lin, Feifei; Zhao, Lijuan; Wang, Yingying; Ye, Yang; Liu, Jia (Planta Medica, 2022)
Lasiocarpine (LAS) and heliotrine (HEL) are two different ester types of toxic pyrrolizidine alkaloids (PAs): open-chain diester and monoester. However, the pharmacokinetics of these two types of PAs in rats have not been reported. In the present study, two LC-MS/MS methods for determining LAS and HEL were established and validated. The methods exhibited good linearity, accuracy, and precision and were then applied to a comparative pharmacokinetic study. After intravenous administration to male rats at 1 mg/kg, the AUC0-t values of LAS and HEL were 336 ± 26 ng/mL × h and 170 ± 5 ng/mL × h. After oral administration at 10 mg/kg, the AUC0-t of LAS was much lower than that of HEL (18.2 ± 3.8 ng/mL × h vs. 396 ± 18 ng/mL × h), while the Cmax of LAS was lower than that of HEL (51.7 ± 22.5 ng/mL × h vs. 320 ± 26 ng/mL × h). The absolute oral bioavailability of LAS was 0.5%, which was significantly lower than that of HEL (23.3%). The results revealed that the pharmacokinetic behaviors of LAS differed from that of HEL.
Keywords: Lasiocarpine; Heliotrine; pyrrolizidine alkaloid; pharmacokinetics